Balancing resources, demand, new challenges, and risks: what is next for the coal industry of Kuzbass - Fridman Yuri (EDP Sciences, 2021)
The article gives an overview of the main external and internal challenges currently facing the coal industry and thus defining where the economy of Kemerovo Oblast – Kuzbass (a key coal-mining center in Russia) is heading. We claim the fourth energy transition as the most important among such challenges, whose basic paradigm is global economic and, in particular, energy systems decarbonization. Countries striving for a low-carbon economy chose coal as their primary target; for instance, Western Europe expects to exit coal-fired power generation by 2030–2035. Experts do not rule out that the world coal market will depend on China and India, the two emerging economies, in the foreseeable future. In this regard, the competitiveness of its coal products compared to solid fuel producers from Eastern Siberia and the Far East is becoming very important for Kuzbass: rivals are ready to supply higher-quality and logistically less expensive coal to the Asia-Pacific markets. In view of the fact that the idea of creating a coal-chemical cluster in Kemerovo Oblast as a long-term driver for the region’s economy has turned out to be untenable, it is now up against the task of forming a new economic doctrine of relations between the coal industry and Kuzbass. We believe it should rest upon the following idea: resources (including coal) have an enormous social and economic value. However, it is only possible to exercise this idea on the principles of harmonized development.